1995
DOI: 10.1016/0020-7292(95)02425-c
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of congenital protein C deficiency with recurrent pregnancy loss

Abstract: A 29-year-old woman experienced unexplained intrauterine fetal death (IUFD) three times, at 16, 27 and 27 gestational weeks. She was found to be protein C-deficient and the existence of infarction in the placenta was suspected at 20 weeks' gestation during her fourth pregnancy. Both heparin and antithrombin III were administered until delivery of a small-for-dates but live baby. Massive infarction in the placenta was evident at term. Anticoagulation with heparin is a useful treatment approach for cases of recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Further, an understanding that a threshold level of maternal PC is critical to sustaining a successful pregnancy may lead to identification of a potential target for drug therapy in certain pregnancy disorders. Since recombinant aPC has been used for treatment of sepsis (21,42,43) and in the management of spontaneous abortion in PC +/-patients (44,45), studies with this low-PC model could add significantly to an understanding of the role of PC in certain pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…Further, an understanding that a threshold level of maternal PC is critical to sustaining a successful pregnancy may lead to identification of a potential target for drug therapy in certain pregnancy disorders. Since recombinant aPC has been used for treatment of sepsis (21,42,43) and in the management of spontaneous abortion in PC +/-patients (44,45), studies with this low-PC model could add significantly to an understanding of the role of PC in certain pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that there is no consensus for therapy for these cases, although Ogasawara et al . concluded that anticoagulation therapy with heparin is a useful treatment when fetal loss is related to PC deficiency 74 …”
Section: Aspirin and Recurrent Pregnancy Loss In Women With Inheritedmentioning
confidence: 99%
“…This dearth of information and lack of published dosing protocols are frustrating. Due to inherent difficulties conducting prospective, randomized, controlled studies in pregnant patients, clinical experience with LMWHs in pregnancy is largely documented as abstracts, letters, [13][14][15][16][17][18][19][20][21][22][23] case reports, [24][25][26][27][28][29][30][31][32][33][34] case series (or experience reports), [35][36][37][38][39]45 and retrospective studies. [40][41][42][43] A few prospective studies 44,[46][47][48][49][50][51][52] were performed, most of which were nonrandomized and/or uncontrolled.…”
Section: Studies Of Low-molecular-weight Heparin Therapy In Pregnancymentioning
confidence: 99%
“…Forty citations were identified; abstracts were 1015 [35][36][37][38][39]45 ; 11 case reports [24][25][26][27][28][29][30][31][32][33][34] ; and 11 letters to the editor. [13][14][15][16][17][18][19][20][21][22][23] According to the U.S. Preventive Services Task Force rating scale, 53 only 2 studies qualified as level I, 50, 52 3 were level II-1, 47-49 3 were level II-2, 39, 46, 51 4 were level II-3, 35, 38, 43, 45 9 were level III, 16,19,22,36,37,[40][41][42]44 and the remaining 19 were classified as other (i.e.…”
Section: Study Designsmentioning
confidence: 99%
See 1 more Smart Citation